Actographic recording system based on a microcomputer - Azpiroz Leehan, J.; Medina Bañuelos, V. (Revista Mexicana de Ingenieria Biomedica, 2018)
A system to study locomotion in small animals is described. The details of the electronic circuit are included and the analysis of the data is explained and it is concluded that the described system is a reliable means for determining the circumdicidal rhythmicity in several species.